An Unusual Heat Wave in North China During Midsummer, 2018 - Lu, Chuhan; Ye, Jiaxin; Wang, Sitao; Yang, Min; Li, Qinqin; He, Wenyue; Qin, Yujing; Cai, JiaXi; Mao, Jia (Frontiers in Earth Science, 2020)
An unusual heat wave was observed at 83% of all recording stations in northeastern China, North China, and Inner Mongolia from mid-July to early August 2018. The local maximum temperatures exceeded 40℃ and brought great impacts to people’s lives and the social economy. Using NCEP/NCAR reanalysis data and station data from the China Meteorological Administration, we study the characteristics and formation of this high-temperature event. The results show that a stable, deep, local, anomalous high over northern China was the main reason for this high-temperature event. A silk-road teleconnection circulation appeared in the upstream part at the midlatitudes of Eurasia and was accompanied by clear energy dispersion of an eastward midlatitude Rossby wave, which favored the divergence of wave energy over Northeast China and led to an increase in geopotential heights and the formation and maintenance of the local anomalous high in North China. Simultaneously, the northern typhoons “Ampil” and “Jongdari” had connections with the local anomalous high, generated obvious secondary meridional circulations, and amplified the downdrafts in the region of the high and the maintenance and intensification of high temperatures. Further analysis revealed that the sea surface temperature anomalies (SSTAs) in the middle of the North Atlantic Ocean in earlier periods would initiate negative vorticity sources on the northwestern side in the high-level troposphere and have a great impact on the generation and maintenance of the high-level silk-road teleconnection.